Religious transformation in modern Asia : a transnational movement - Kim, David W. (Numen Book Series, 2015)
This volume explores the religious transformation of each nation in modern Asia. When the Asian people, who were not only diverse in culture and history, but also active in performing local traditions and religions, experienced a socio-political change under the wave of Western colonialism, the religious climate was also altered from a transnational perspective. Part One explores the nationals of China (Taiwan), Hong Kong, Korea, and Japan, focusing on the manifestations of Japanese religion, Chinese foreign policy, the British educational system in Hong Kong in relation to Tibetan Buddhism, the Korean women of Catholicism, and the Scottish impact in late nineteenth century Korea. Part Two approaches South Asia through the topics of astrology, the works of a Gujarātī saint, and Himalayan Buddhism. The third part is focused on the conflicts between 'indigenous religions and colonialism,' 'Buddhism and Christianity,' 'Islam and imperialism,' and 'Hinduism and Christianity' in Southeast Asia.